Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1088/0957-4484/24/23/235402
|View full text |Cite
|
Sign up to set email alerts
|

Realization of high performance silicon nanowire based solar cells with large size

Abstract: We report the realization of high performance silicon nanowire (SiNW) based solar cells with a conversion efficiency of 17.11% and a large size of 125 × 125 mm(2). The key factor for success lies in an efficient approach of dielectric passivation to greatly enhance the electrical properties while keeping the advantage of excellent light trapping of the SiNW structure. The suppression of carrier recombination has been demonstrated through the combination of the SiO2/SiNx stack, which exhibits a good passivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 30 publications
(53 reference statements)
6
71
0
Order By: Relevance
“…Fig. 4 (b) shows that τ eff of the one-step-MACE-smoothened N/M-Strus for both the as-etched and SiN x :H-passivated cases, slightly decrease with increasing β, which is consistent with the previous results [19][20][21]. Obviously, all the four series for the as- where Kerr Auger recombination model [37] is considered.…”
Section: Electrical Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…Fig. 4 (b) shows that τ eff of the one-step-MACE-smoothened N/M-Strus for both the as-etched and SiN x :H-passivated cases, slightly decrease with increasing β, which is consistent with the previous results [19][20][21]. Obviously, all the four series for the as- where Kerr Auger recombination model [37] is considered.…”
Section: Electrical Analysissupporting
confidence: 88%
“…However, the optical advantage of Si nanostructures has not been facile to be fully converted into the η-gain of solar cells [4][5][6][7][8][9][10][11][12][13][14][15], which is mainly ascribed to the poor electrical properties, i.e., high recombination on the surface and in the bulk of Si nanostructures. Over the past several years, substantial progresses in improvement of the electric performance have been made by carrying out various process methods such as the surface passivation [16][17][18][19][20], properly increasing sheet resistance [21,22] and optimization of morphology of mc-Si nanostructures [11,13,14,19]. Using the optimized textured structure, Zhong et al, [23] and Xiao et al, [24] have reported ηs of 15.99% and 17.46% for mc-Si nanostructures based solar cells with the standard solar wafer size of 156 Â 156 mm 2 through reactive ion etching (RIE), respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1. Solar cell devices with conversion efficiencies of around 12% were reported for a nanowire junction geometry [15,16], whereas the use of nanowires as an anti-reflection texture for 300 µm thick substrates enabled device efficiencies of 18% [17,18]. However, too many research challenges still need to be addressed, before a commercial product based on nanowires can be introduced: mainly, the stability of the junction formation and the effective surface passivation, but also practical issues, such as the rapid scaling and the integration of nanowires into modules, need to be better understood and further improved.…”
Section: The Main Light-trapping Approaches 221 Non-diffractive Tecmentioning
confidence: 99%
“…Many researchers have reported that SiNW arrays have high light absorptance and are promising as absorber layers for solar cells. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, despite their excellent optical advantages, the conversion efficiency of SiNW-based solar cells is yet insufficient because of serious surface recombination due to their high surface area-to-volume ratio. Accordingly, it is necessary to obtain high absorptance with short wires from the perspective of not only an etching margin but also surface recombination.…”
Section: Introductionmentioning
confidence: 99%